Vincristine and prednisone regulates cellular and exosomal miR-181a expression differently within the first time diagnosed and the relapsed leukemia B cells. (2020) - Haque, Shabirul; Vaiselbuh, Sarah R.
Abstract: We explored the effect of vincristine and prednisone on cellular and exosomal miR-181a expression in first time diagnosed leukemia and relapsed leukemia. Vincristine and prednisone induced apoptosis/pro-apoptotic genes in first time diagnosed leukemia, and suppressed the cellular and exosomal miR-181a expression. In contrast, vincristine and prednisone could not induce apoptosis/pro-apoptotic genes in relapsed leukemia, and could not change the expression of cellular or exosomal miR-181a. In conclusion, the non-suppressive nature of miR-181a in relapsed leukemia might contribute to the chemo-resistance and this suggests a potential role of miR-181a-inhibitor along with the chemotherapy in the treatment of relapsed leukemia.